Temporal Regulation of Cytokines by the Circadian Clock - Atsuhito Nakao (Journal of Immunology Research)
Several parameters of the immune system exhibit oscillations with a period of approximately 24 hours that refers to “circadian rhythms.” Such daily variations in host immune system status might evolve to maximize immune reactions at times when encounters with pathogens are most likely to occur. However, the mechanisms behind circadian immunity have not been fully understood. Recent studies reveal that the internal time keeping system “circadian clock” plays a key role in driving the daily rhythms evident in the immune system. Importantly, several studies unveil molecular mechanisms of how certain clock proteins (e.g., BMAL1 and CLOCK) temporally regulate expression of cytokines. Since cytokines are crucial mediators for shaping immune responses, this review mainly summarizes the new knowledge that highlights an emerging role of the circadian clock as a novel regulator of cytokines. A greater understanding of circadian regulation of cytokines will be important to exploit new strategies to protect host against infection by efficient cytokine induction or to treat autoimmunity and allergy by ameliorating excessive activity of cytokines.